Pengaruh Laju Pertumbuhan Penduduk dan Inflasi Terhadap Kemiskinan Di Indonesia Tahun 2001-2021 - Sanny Feria Juliana; Yulian Rinawaty Taaha; Feliks Arfid Guampe* (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine the effect of population growth rate and inflation on poverty in Indonesia. The data used in this study is time series data starting from 2001-2021. This study used secondary data obtained from publication documentation from the Indonesian Central Bureau of Statistics (BPS). The data analysis method used is multiple linear regression with the E-Views 9 program. The results showed that the partial rate of population growth had a negative and insignificant effect on poverty. The variable inflation partially has a positive and significant effect on poverty. Simultaneously, the rate of population growth and inflation have a significant effect on poverty in Indonesia. The value of the coefficient of determination shows that the rate of population growth and inflation is able to explain poverty by 33.77%.